2009
DOI: 10.1002/cbdv.200800253
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of the Essential Oil from the Leaves of Croton regelianus and Its Component Ascaridole

Abstract: Croton regelianus Muell. Arg., popularly known as 'velame-de-cheiro', is a native plant from the Northeast of Brazil used in folk medicine to treat diseases of different kinds, including malignant tumors. In this study, the in vitro and in vivo antitumor effects of the essential oil from the leaves of C. regelianus and ascaridole, one of the main constituents, were investigated. In vitro, the essential oil and ascaridole displayed cytotoxicity, showing IC(50) values in the range of 22.2 to 48.0 microg/ml in HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 29 publications
2
28
0
3
Order By: Relevance
“…CCRF-CEM; HL60; MDA-MB-231 Antineoplastic effects [170] Modest inhibition in sarcoma 180 tumor model [171] Bisacurone [190], inhibited DNMT2 activity, reduced HDAC1; induced p53 [191] Augmented efficacy of docetaxel and restored sensitivity to anti-androgen therapy in xenograft mice [192] Ganoderic acid T (GA-T)…”
Section: Phytochemicals and Discovery Of Anticancer Drugsmentioning
confidence: 99%
“…CCRF-CEM; HL60; MDA-MB-231 Antineoplastic effects [170] Modest inhibition in sarcoma 180 tumor model [171] Bisacurone [190], inhibited DNMT2 activity, reduced HDAC1; induced p53 [191] Augmented efficacy of docetaxel and restored sensitivity to anti-androgen therapy in xenograft mice [192] Ganoderic acid T (GA-T)…”
Section: Phytochemicals and Discovery Of Anticancer Drugsmentioning
confidence: 99%
“…Ascaridole showed antitumor activity in sarcoma 180 murine model which signified the ethnopharmacological use of this plant for the treatment of cancer [21]. Fifty three phytochemicals isolated from plants were tested for their differential cytotoxic effects in the cell lines which were having defect in the nucleotide excision repair genes ERCC6 or XPC, and from the result it was found that ascaridol was the most effective [22].…”
Section: Anticancer Activity Of Ascaridolementioning
confidence: 99%
“…Entre elas temos C. regelianus com atividade anticâncer (Bezerra et al, 2009) e Securinega suffruticosa (Euphorbiaceae), típica do cerrado brasileiro, com atividade antitumoral (Yuan et al, 2005;Mesquita, 2010). Este grupo não é muito comum a Croton, tendo sido detectada em C. salutaris, com 12-hidroxi-13-metilpodocarpa-9,11,13-trien-ona (Itokawa, 1991) e em C. regelianus, (5β,8α,10α)-8-hidroxi-13-metilpodocarpa-9(11),13-diene-3,12-diona (Torres et al, 2010).…”
Section: Fórmula MMunclassified
“…Os podocarpanos apresentam até o momento, distribuição restrita, tendo sido detectado apenas no Brasil em espécies coletadas nos estados do Ceará (C. regelianus - Bezerra et al, 2009) e São Paulo (C. salutaris - Itokawa et al, 1991). Com os dados deste estudo, diterpenos com este tipo de esqueleto foram identificados para mais cinco espécies de Croton coletadas nos estados de Minas Gerais (C. ceanothifolius e C. pseudoadipatus), São Paulo (C. pallidulus var.…”
Section: Oh Ch3 H2cunclassified